Life cycle assessment of a fluorescent lamp luminaire used in industry – a case study. (August 2014) - Tähkämö, L; Bazzana, M; Zissis, G; Puolakka, M; Halonen, L
Environmental impacts of light sources and control gears have been analysed in several life cycle assessments (LCAs). In contrast, this paper analyses the environmental impacts of an entire fluorescent lamp/luminaire combination. The environmental impacts of a fluorescent lamp luminaire with two T5 lamps and an electronic ballast are analysed in a variety of potential environmental impacts. The results show that the energy consumption during use dominates the total environmental impacts by 93% on the average, while manufacturing accounts for 7% and end-of-life less than 1%. The importance of energy consumption is dependent of the used energy source. Compared to a previous LCA of fluorescent lamp luminaire, the division of the results into life cycle stages is similar but there are differences in the numerical results.